Gehören Menschenrechte und Menschenwürde zusammen? - Kaufmann, Matthias (RESEARCH TRENDS IN HUMANITIES Education & Philosophy, 2014)
The concept of human dignity seems to be closely connected to the idea of human rights. But whereas human rights are at least from an institutional point of view well established, the concept of human dignity is often seen as either arbitrary and superfluous or fundamen-talistic. The paper shows that human rights and human dignity had different histories for a long time but are nowadays intrinsically connected. The concept of human dignity implies a certain core of human rights and offers the chance to understand that there is not one overall view of human rights for all times and places, but that human rights discourse always has to be open to modifications according to the conditions of application. After first mentions in Cicero and Seneca, more diversified uses by Aquinas and Pico della Mirandola, the talk of human dignity finds its current meaning in Kant’s philosophy, often connected to the formula of persons as ends in themselves. This seems to be one of the systematic connections to the tradition of human rights which has its roots in the semantic shift of the word ius in 11th and 12th century from an objective order to claims of different kinds. This kind of argument is used in different contexts throughout the following centuries and transformed in 16thand 17th century into claims of citizen’s rights and human rights. Another connection between the two concepts is given by Martha Nussbaum’s capability approach which is not restricted to human reason. The criticisms against the two conceptions are also different, but connected: Human rights are accused to foster individualism and egoism against the community and declared to be an erroneous development of western culture. Human dignity is seen as an indicator of human hubris towards other creature, based on metaphysical assumptions and a part of “slave morals”, contempt by men like Nietzsche. Both criticisms seem not to be adequate. In the end, the concept of human dignity gives an instrument to defend as much as possible of human integrity in situations where human rights are violated, limited or in one or the other way under pressure.